THE RELATIONSHIP OF LEADERSHIP STYLE, COMPETENCE AND COMPENSATION TO EMPLOYEE PERFORMANCE IN SELUMA REGIONAL SECRETARIAT - Herwin Susanto; Karona Cahya Susena; Abdul Rahman (Penerbit Jurnal Indonesia, 2020)
This study government organizations are demanded for Good Governance in providing services to the community. Some things that can improve employee performance in the form of leadership style, competence and compensation. This study shows that leadership style variables in government organizations have a positive and significant relationship to employee performance, competency variables in government organizations have a positive and significant relationship to employee performance. While compensation variables have a significant effect one mployeeper formance. Based on the results of the leadership style variables it is known that the value of t is greater than t table ¬; (4,71452> 1,66055) means that the leadership style has a significant relationship to the Sekretariat Daerah Kabupaten Seluma. This explains that there is a fairly close relationship between leadership style and employee performance at the Sekretariat Daerah Kabupaten Seluma. If the leadership style is improved, employee performance will increase. Based on the results of the Competency variable, it is known that the t value is greater than t table; (7,62073> 1,66055) means that competence has a significant relationship with employee performance at the Sekretariat Daerah Kabupaten Seluma. This explains that there is a close relationship between competence and employee performance at the Sekretariat Daerah Kabupaten Seluma If competency is improved, employeeper formance will increase. Based on the compensation results it is known that the calculated t value is greater than t table; (9,70344> 1,66055) means that compensation has a significant relationship to the performance of employees at the Sekretariat Daerah Kabupaten Seluma. This explains that there is a close relationship between compensation for employee performance at the Sekretariat Daerah Kabupaten Seluma, if compensation is increased then employee performance will increase.